Faktor Penentu Penggunaan Sistem Informasi dan Dampaknya Terhadap Kinerja Perusahaan - Alexandra Adriani Widjaja (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2019)
The application of information technology is intended to support the company's primary activities. The information produced must be able to be used in a real way to improve company performance. The key to the success of information technology utilization is the ability to use information generated by the system in every company decision making. Previous studies show that the use of information is strongly influenced by the ability of individuals and the environment around the individual. Therefore, this study aims to examine the influence of individual competencies and the opportunity to share knowledge (knowledge sharing) with the use of information, and test whether the use of information influences the performance of the company. This study also examined the indirect relationship between knowledge sharing and company performance. Tests are carried out using Structural Equation Modeling (SEM). The results of this study indicate that knowledge sharing has a significant effect on the use of information. The use of information also has a significant effect on company performance. On the other hand, this study found that individual competencies did not have a significant effect on information use. This study also cannot prove the indirect influence of knowledge sharing variables on company performance through information usage variables.